Store Atmosphere and Price on Purchase Decisions (Study of Kopi Ruang Hati Consumers in Sangatta City) - Nababan, Ruth Tesalonika; Rahmah, Dian Dwi Nur; Rahman, Nadya Novia (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The many coffee shops spread across Indonesia provide a change to a more modern and more practical lifestyle. The development of the coffee shop business has created intense competition in the business world to win consumers with their purchasing decisions. The paper seeks to investigate how the store environment and pricing impact the buying choices of franchise customers at Kopi Ruang Hati in Sangatta City. The study will employ a quantitative research method. The study focused on Kopi Ruang Hati consumers selected through simple random sampling. Data collection methods used are store atmosphere, price, and purchase decisions. The analysis method utilized is multiple linear regression. The findings uncover that: (1) an impactful outcomes was observed as a result of purchasing decisions and store atmosphere towards prices with a F statistic = 17,188 > F table = 3.08 and p = 0.000 and had an influence contribution (R2) of 24.8%; (2) no influences are triggered by store atmosphere on purchasing decisions with a coefficient of beta (β) = 0.067, t statistic = 0.773 > t table = 1.983, and p = 0.441 (p < 0.05); and (3) The price has a major impact on the choices consumers make when buying with the beta coefficient (β) = 0.479, t statistic = 5.489 > t table 1.983, and p = 0.000 (p < 0.05).